Plastic injection moulding of hypodermic needles - Ang, Poh Lin (2009)
Metal hypodermic needle is commonly used to perform in vivo drug delivery or blood extraction application. However, one of the most serious drawbacks such as the reuse of hypodermic needle becomes the major source of infections. Therefore, a concept of replacing the metal hypodermic needles with plastics is carried out in order to reduce the reuse of contaminated needles.